Development in Social Cultural Status of Tamang Women (A Brief Study of Phungling Municipality Ward No. 10, Taplejung, District) - Khatri, Chakra Bahadur (Nepal Journal of Multidisciplinary Research, 2021)
There is great values of development of socio-cultural and economic status of indigenous women like Tamang, limbus for the holistic development in Nepal. The perfect socio-cultural and economic status only can determine the level of development. This paper tries to carry out the sketch of developing condition of socio-cultural status of Tamang women in Phungling Municipality Ward No. 10. The paper is based on both primary and secondary data. Most of the data are taken from interview questionnaires. The relevancy of this paper goes to find out the developing stages of socio-cultural and economic status of Tamang women for the better livelihood of Tamang community.